The Effect of Personal Hygiene, Safety, Security and Health (K3) and Service Quality on Customer Satisfaction at Palinggihan Restaurant, Cirebon - Tarigan, Emenina; Sembiring, Vienna Artina; Prabandari, Wijayanti Dewi (Institut Pariwisata Trisakti, 2021)
This study aims to determine Personal Hygiene, Safety, Security and Health (K3) and Service Quality on Customer Satisfaction at Palinggihan Restaurant Cirebon. The research method used is a quantitative method, with a descriptive approach. Sampling using accidental sampling technique. The number of respondents is 100 people. The results of this study were Personal Hygiene, Safety, Security and Health (K3) had no significant effect on customer satisfaction, while service quality had a significant effect on customer satisfaction. This is because consumers who come to the Palinggihan Cirebon Restaurant only visit no more than five times, so they don't care about Personal Hygiene, Safety, Security and Health (K3). The service procedures in the restaurant are carried out properly and correctly by the employees of the Palinggihan Cirebon Restaurant, namely greeting, placing guests, serving menu books, taking orders, serving food and drinks, billing system, thanking people and clearing the table. Suggestions from this research are (1) Restaurant owners need to plan Personal Hygiene, Safety, Security and Health (K3) training for their employees; (2) A manager or restaurant supervisor conducts morning briefing for employees to provide reports on yesterday's sales and favorite and upselling menus (offering menus to consumers). Keywords: Personal Hygiene, Safety, Security and Health (K3), Service Quality, Consumer Satisfaction